(untitled) (International Journal of Physiotherapy, 2016)
Background: Forward head is a common postural fault of the cervical spine that can be assessed using the photogrammetry method. This is a valid, popular and feasible clinical method. Although forward head is primarily a sagittal plane postural fault, deviations in other planes may result in measurement errors when photos are captured from only one side. Therefore, the purpose of this study was to investigate whether forward head assessment by photogrammetry taken from the right (Rt) or left (Lt) sides of the body would differ. Methods: One hundred thirty two healthy adults were assessed from standing and 90 were assessed from sitting positions. In addition, 41 patients with mechanical neck pain were assessed from standing and 56 from sitting positions. Three profile photos were captured from each side in standing and sitting positions. Photos were then digitized before they were analyzed using the kinovea software to measure the craniovertebral (CVA) and gaze angles. Results: In healthy adults, the CVA was not significantly different across sides (p>0.05) whereas the gaze angle was different regardless of the testing position (p <0.05). For patients with mechanical neck pain, CVA differed in standing (p <0.05) but not in sitting position (p >0.05), whereas the gaze angle did not differ regardless of the testing position (p >0.05). Conclusion: Measurement of CVA and gaze angles in sitting and standing is not consistent across sides, depending on the population tested. Assessors should be conservative and consider taking photos from both sides to assess the severity of forward head position using the photogrammetric method.